Synthesis, Spectroscopic Characterization, Antibacterial and Short Term in vitro Cytotoxicity Studies of Copper(II) Complexes of Novel Tridentate N,N,S Donor Ligand 2-Benzoylpyridine-N(4),N(4)-(N,N-diethyl-N-methylamine-2,2’-diyl)thiosemicarbazone - Mathew, Janey Mary; Philip, Varughese; Thomas, Jesty (Asian Journal of Chemistry, 2019)
A tridentate N,N,S-donor ligand, 2-benzoylpyridine-N(4),N(4)-(N,N-diethyl-N-methylamine-2,2'-diyl)thiosemicarbazone (Hbptsc) has been synthesized and characterized by elemental CHN analysis, UV-visible, FT-IR and 1H NMR spectroscopy. Copper(II) complexes of the ligand, Hbptsc synthesized have been characterized by elemental analysis, UV-visible spectra, FTIR spectra and EPR spectroscopic simulation. The complexes hold the stoichiometry of the type [CuLX] where X= Cl (1), NO3 (2), SO4 (3), N3 (4), SCN (5) confirmed by the molar conductivity studies of 10-3 M solutions in DMF at room temperature. The EPR spectra of the complexes recorded in DMF at 77 K shows an axial type spectra with two distinct g-values, g|| and g⊥ indicating a four coordinated planar geometry. The antimicrobial studies of the copper(II) complexes shows an appreciable activity against both gram positive and gram negative bacteria using streptomycin as positive control. The short term in vitro cytotoxicity studies following trypan blue dye exclusion method exhibits pronounced activity against the Dalton’s Lymphoma Ascites tumour cells extruded from the peritoneal cavity of mice.